A Review on Effect of Surface Finish and Cooling Rate on Solder Joint Reliability - Hardinnawirda, Kahar; Zetty Akhtar, Abd Malek; Siti Rabiatull Aisha, Idris (WIT Press, 2017)
The increasing environmental concern over the toxicity of lead (Pb) combined with strict regulations, the use of lead-based solders providing an inevitable driving force for the development of lead-free solder alloys. Many studies have been conducted for evaluation of the solder joint reliability with respect to solder alloys and surface finishes. However, as the demand of electronic devices is increasing, there is a need to improve the mechanical properties of the solder joint in order to keep up with the current evolution of electronic device's technology. In this study, the effect of surface finish and cooling rate on solder joint reliability using Nickel-based surface finish was summarizes. Study was focusing on Nickel based surface finish (ENIG and ENEPIG) with different cooling medium, slow (furnace), medium (air) and fast (water). It was found that the type of surface finish and the cooling rate can change the morphology of the solder intermetallic compound (IMC) and directly changes the solder joint mechanical properties. Faster cooling rate was reported to provide finer IMC grains which might be translated into a better solder joint strength. The findings presented here may provide a better understanding for a further study and facilitate improvements in term of solder joint reliability.